2010
DOI: 10.1007/s11033-010-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

The expression and activation of ERK/MAPK pathway in human esophageal cancer cell line EC9706

Abstract: While there have been more and more studies concerning mitogen-activated protein kinases (MAPKs) signaling pathways, which control many cellular complex programmes, such as cell proliferation, differentiation, cell death and embryogenesis. However, few studies are carried out about expression and activation of classical MAPKs, extracellular signal-regulated kinase1/2 (ERK1/2) in human esophageal cancer cell line. Therefore, in the present study, we investigated the expression and activation of ERK1/2 in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Notably, ERK, a widely expressed signaling molecular, is pivotal for cellular proliferation, differentiation and survival in various cells, including EPCs [ 30 32 ], which can be activated during cell angiogensis induced by Toll-like receptor 2 in endothelial cells [ 33 ]. Our data demonstrated that phosphorylated ERK expression in EOCs from CAD patients was significantly lower compared with healthy subjects, and upregulation of CXCR7 by gene transfer can reverse the decreased phosphorylated ERK level in EOCs from CAD patients, indicating that ERK was the downstream signaling of CXCR7 pathway in EOCs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ERK, a widely expressed signaling molecular, is pivotal for cellular proliferation, differentiation and survival in various cells, including EPCs [ 30 32 ], which can be activated during cell angiogensis induced by Toll-like receptor 2 in endothelial cells [ 33 ]. Our data demonstrated that phosphorylated ERK expression in EOCs from CAD patients was significantly lower compared with healthy subjects, and upregulation of CXCR7 by gene transfer can reverse the decreased phosphorylated ERK level in EOCs from CAD patients, indicating that ERK was the downstream signaling of CXCR7 pathway in EOCs.…”
Section: Discussionmentioning
confidence: 99%
“…The other crucial cell survival pathway is MAPK. The MAPK family, which is well known to be involved in the occurrence, progression, and metastasis of tumors, includes ERK1/2, p38, and JNK [25][26][27]. ERK1/2 was found to be expressed more highly in ESCC tissues than in adjacent normal esophageal tissues [28].…”
Section: Discussionmentioning
confidence: 99%
“…The ERK/MAPK signaling pathway is widely expressed in many tissues and cells, and can regulate cell proliferation, the cell cycle, apoptosis, migration and invasion, and many other biological processes (22,23). Excessive activation of the ERK/MAPK signaling pathway can cause abnormal proliferation, apoptosis and differentiation of cells, and thus is associated with tumor occurrence, progression and metastasis, including gallbladder carcinoma (22), esophageal cancer (24), and breast cancer (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%